KONFIGURASI KINEMATIK DAN DINAMIK SIMULATOR KENDALI TURRET - Munadi, Munadi; Tauviqirrahman, Mohammad (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2007)
Technology development is a fundamental need for a country, especially in the defense area. To catch uptechnological with advancement, it requires many skills according to the vast and complex defence technologydevelopment. We need to start basic research in the defense area to minimize our dependence to foreign countries.One important device that is still imported is the gun turret. This equipment can be placed in a tank or a battleship to control gun, cannon or missile launcher.The design of a turret control simulator is a preliminary stage in designing the real turret. This simulatorimplements knowledge from robotic science which study the kinematic and dynamic aspects of a robot. From thekinematic aspect, the speed of each link is known. From the dynamics aspect, the torque for each joint from theactuator, which due to the hydraulic force or a hydraulic torque, is known. The Newton-Euler method is used to solvethe dynamic equation.